Vegetation diversity and carbon stock in gold mining reclamation area in Pongkor, West Java, Indonesia - SYAIFUL HABIB; MAHAWAN KARUNIASA; LULUK SETYANINGSIH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Habib S, Karuniasa M, Setyaningsih L. 2025. Vegetation diversity and carbon stock in gold mining reclamation area in Pongkor, West Java, Indonesia. Biodiversitas 26: 4932-4945. Global greenhouse gas emissions set a new record of 57.1 GtCO2e in 2023, an increase of 1.3 percent from 2022 levels. One of the efforts to mitigate carbon dioxide emissions in the mining industry can be done by reclaiming ex-mining land through revegetation. The objective of study was to analyze vegetation diversity and carbon dioxide absorption in the reclamation area of gold mining in Pongkor, West Java Province, Indonesia. The method used for this study was quantitative observation by measuring the number of species, density, frequency and growth of vegetation to calculate diversity index (H'), vegetation biomass and its ability to absorb carbon in the post-mined area reclaimed from 2014 to 2023 covering an area of 21.6 ha. The results of the study showed that the Shanon-Wiener diversity index (H') of tree, pole, sapling and lower-level plant was in the moderate category (1<H'<3). The reclamation area of 21.56 ha was able to absorb carbon dioxide cumulatively of 3,237.98 tons or contributed 5.89% of CO2 emissions by the mining company. Reclamation in the gold mining area is able to restore the ecology of vegetation and absorb carbon dioxide emissions generated from mining activities. However, 10 years of reclamation and revegetation activities still does not offset carbon emissions resulted from the mining activities, suggesting a longer period of restoration with strong monitoring efforts to fully compensate the carbon footprint.